Wizerunek masonerii jako organizacji satanistycznej na przykładzie publikacji Feliksy Eger - Rosiak, Katarzyna (Humaniora. Czasopismo Internetowe, 2021)
In my paper I’m analysing an image of freemasonry in works of Feliksa Eger who wrote on this subject in XIX century. This paper is a an input to increase knowledge about an image of freemasonry and also about a phenomena of anti-masonry, understood as a world view choice, in which masonry becomes a source of all the evil on the world. The aim of research was finding an answer on a question if it is possible to find in Feliksa Eger’s publications an influence of confabulations of Léo Taxil, creator of satanistic black legend of freemasonry. Analysis of Feliksa Eger’s publications, using such scientific methods as content analysis and image analysis proves that in her writings there were used motives described by Taxil. Additionally comparative analysis of texts also pays attention to an evolution of freemasonry image from rather negative image of freemasons as national enemies (category connected with a church’s doctrine) to a very negative pop-cultural image in which freemasons are understood as a power of New World Order, category formed by Léo Taxil’s publications. At the beginning the author presents masonry only as an organization endeavouring to take over the world and destroy Christianity. But in her last publication she describes freemasons as a Satanic sect ruled by Albert Pike. Satanic image of freemasonry visible in Eger’s works pays attention to the fact, how fast the myths created by Taxil were taken by other authors, copied and distributed by them.